Factors Associated with Academic Performance in Undergraduate Health Sciences Students Enrolled in the Human Anatomy Course [Factores Asociados Al Rendimiento Académico en la Asignatura de Anatomía Humana en Estudiantes de Pregrado de Ciencias de la Salud] - Lopez-Alegria, F (Universidad Nacional de Colombia, 2021)
Introduction: Human anatomy is a core subject that poses a great academic challenge for students who are admitted to the health sciences undergraduate degree programs. Objective: To know the socio-academic profile of first-year students of several health sciences undergraduate programs and to assess the association between, on the one hand, academic performance during secondary education, study habits and performance in the university admission science test, and, on the other, academic performance in the human anatomy course. Materials and methods: Cross-sectional correlational study conducted in 2018. The study population consisted of 306 first-year students enrolled in 7 health sciences undergraduate programs offered by the Faculty of Medical Sciences of a public university in Santiago de Chile, Chile. The Pearson correlation coefficient was used to determine the correlation between the variables of interest. Also, a multiple linear regression analysis was performed to establish the factors significantly associated with the final grade obtained in the course. A level of significance of p<0.05 was considered. Results: The mean age of the participants was 19.8 years, 98.6% were single, and 65.3% were female. A significant association was observed between the final grade obtained in the course and the score obtained in the university admission test (p=0.000) and the high school grade point average (p=0.001); however, this association was not significant with the variables considered as study habits. Conclusion: Academic performance in the human anatomy course was associated with the students’ prior knowledge, but not with their study habits. Thus, educational interventions in this university should focus more on leveling students’ knowledge, rather than on optimizing their study habits. © 2021, Universidad Nacional de Colombia. All rights reserved.
Keywords: Academic Performance; Anatomy; Chile (MeSH); Students, Health Occupations; Universities